2013
DOI: 10.1186/2049-2618-1-15
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intestinal microbial community structure on disease manifestation in IL-10-/- mice infected with Helicobacter hepaticus

Abstract: BackgroundThe aberrant inflammation that is the hallmark of the inflammatory bowel diseases (IBD) is associated with several factors, including changes in the intestinal microbiota. Here, we confirmed that an intestinal microbiota is needed for development of typhlocolitis in Helicobacter hepaticus infected IL-10-/- C57BL/6 mice, and investigated the role of the microbiota in modulating disease.ResultsWe altered the murine microbiota by treatment with the antibiotics vancomycin or cefoperazone prior to H. hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 68 publications
1
33
1
Order By: Relevance
“…Using T-RFLP and 16S rRNA sequencing, two previous studies showed that H. hepaticus becomes a dominant member of the microbiota and reduced microbial diversity within the mouse intestinal tract of WT and IL-10 KO mice [44], [45]. In this study, H. hepaticus infection did not significantly affect the alpha diversity in WT mice after 1 year of infection, and had a low relative abundance.…”
Section: Discussioncontrasting
confidence: 38%
“…Using T-RFLP and 16S rRNA sequencing, two previous studies showed that H. hepaticus becomes a dominant member of the microbiota and reduced microbial diversity within the mouse intestinal tract of WT and IL-10 KO mice [44], [45]. In this study, H. hepaticus infection did not significantly affect the alpha diversity in WT mice after 1 year of infection, and had a low relative abundance.…”
Section: Discussioncontrasting
confidence: 38%
“…To further delineate the role of NLRP6 in modulating intestinal inflammatory responses, we generated mice doubly deficient in NLRP6 and IL10. IL10 −/− B6 mice at our facility are resistant to the development of colitis (Nagalingam et al, 2013)(Figure S1A). However, by 8 weeks of age, IL10 −/− Nlrp6 −/− mice developed spontaneous colitis (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the intestinal microbiota was shown to be essential for the development of typhlocolitis in H. hepaticus infected IL-10 deficient mice; in addition, where disease could be initiated, severity of histopathological lesions varied significantly in the presence of different microbial communities 32 . While H. hepaticus drives immune responses in this model, the specific structure of the microbiota was believed to modulate host gene expression pathways that lead to chronic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%